Older Adults in Sport: Senescence, Stereotypes, and Ageism - Goriup, Jana (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
Aging is an individualized and complex process; nevertheless, it is often viewed through the lens of stereotypes, particularly in Western postmodern societies. Stereotypes about older adults play a significant role not only in shaping public perceptions and influencing social interactions but also in affecting their participation in sport and their self-perception as members of this age group. The social significance of sport stems from its well-documented contributions to public health, socialization, and economic development. The growing recognition of the importance of sport and physical activity for older adults is also reflected in the initiatives of the World Health Organization (WHO), particularly the Global Action Plan on Physical Activity 2018–2030. However, sports participation among older adults must be tailored to their age, health status, physical condition, and individual capabilities. Unlike professional athletes, older adults generally engage in sport not for employment or financial gain but for enjoyment, health, and personal well-being. Research has identified a range of motivations for maintaining regular physical activity in later life, including enhancing physical fitness, managing age-related changes, promoting healthy aging, and fostering social engagement and overall quality of life.